Perubahan Peran Perempuan Setelah Pengadaan Tanah untuk Pembangunan Yogyakarta International Airport: Kasus Kalurahan Kebonrejo di Kabupaten Kulonprogo, Daerah Istimewa Yogyakarta - Fairuz Nabila; Mohamad Shohibuddin; Endriatmo Soetarto (BHUMI: Jurnal Agraria dan Pertanahan, 2021)
Abstract: Women are one of the parties being affected by the process of land acquisition for the construction of public infrastructure. This article aims to analyse the change of women role after the implementation of land acquisition for the construction of Yogyakarta International Airport in Kulonprogo regency, Special Region of Yogyakarta. The research is carried out in Kebonrejo village, Temon district using quantitative approach supported by qualitative approach. Quantitative data are collected through a survey among 30 female respondents in the households selected by a simple random sampling and analysed through Rank Spearman test, while qualitative data are obtainded through documents review, participant observation and depth interview with key informants. The research findings demonstrate that there is a weak relationship between the participation of women throughout the implementation of land acquisition and the change of women role after the completion of land acquisition. This is due to the fact that despite there is a strong emphasize of public consultation and participation in the regulation of land acquisition, the will and power of the government is very strong and could not be influenced by the whole affected community. In addition, the process of land acquisition itself often put aside women’s specific aspiration and intereset. Consequently, a relative equal gender relation within the household during land acquisition process didn’t have any effect throughout the process and afterward. Keywords: women participation, the roles of women,  land acquisition, development of public infrastucture.   Intisari: Perempuan adalah salah satu pihak yang terimbas oleh pengadaan tanah untuk pembangunan infrastruktur publik. Artikel ini bermaksud untuk menganalisis ,perubahan peran perempuan setelah pengadaan tanah untuk pembangunan Yogyakarta International Airport di Kabupaten Kulonprogo, Daerah Istimewa Yogyakarta. Penelitian lapangan dilakukan di Kalurahan Kebonrejo, Kapanewon Temon dengan menggunakan pendekatan kuantitatif yang didukung pendekatan kualitatif. Data kuantitatif diperoleh dari survei atas 30 responden perempuan dalam rumah tangga yang dipilih secara simple random sampling dan diolah dengan uji Rank Spearman, sementara data kualitatif diperoleh melalui studi dokumen, pengamatan terlibat dan wawancara mendalam dengan para informan. Hasil penelitian menunjukkan bahwa terdapat hubungan yang lemah antara keterlibatan perempuan selama proses pengadaan tanah untuk pembangunan Yogyakarta International Airport dengan peran perempuan setelah pengadaan tanah. Ssekalipun keharusan konsultasi dan partisipasi publik sangat ditekankan dalam regulasi pengadaan tanah, namun kehendak dan kekuasaan yang kuat dari pemerintah membuat proses pengadaan tanah tidak dapat dipengaruhi oleh masyarakat terdampak secara keseluruhan. Selain itu, proses pengadaan tanah itu sendiri abai terhadap aspirasi dan kepentingan spesifik kaum perempuan. Akibatnya, relasi gender yang relatif setara di level rumah tangga selama proses pengadaan tanah tidak memiliki hubungan apa pun sepanjang proses tersebut maupun setelahnya.  Kata Kunci: keterlibatan perempuan, peran perempuan, pengadaan tanah, pembangunan infrastruktur publik.